SPECTRAL AND PHOTOMETRIC STUDIES OF MRK6 AND MRK1040 IN THE OPTICAL RANGE - Shomshekova, S.A.; Denissyuk, E.K.; Kondratyeva, L.N.; Serebryanskiy, A.V.; Aimanova, G.K.; Aktay, L. (Eurasian Physical Technical Journal, 2025)
This paper is dedicated to the study of variability in active galactic nuclei, which play a key role in understanding the physical processes occurring in their central regions. This research focuses on the analysis of photometric and spectral variability of two Seyfert galaxies, MRK 6 and MRK 1040, based on archival and modern observations. For the first time, the results of photometric observations of MRK 6 have been processed, with special attention given to the profiles of emission lines and the identification of additional spectral components that may indicate gas outflows. The velocity dispersions of each emission-line component have been determined for the studied galaxies. In some profiles of Hα and Hβ, their velocity dispersions and corresponding line-of-sight velocities have been estimated, which may indicate the outflow of matter from the central regions of the galaxies.